Safety of endovascular thrombectomy in patients receiving non-vitamin K antagonist oral anticoagulants - Purrucker, Jan; Wolf, Marcel; Rizos, Timolaos; Khan, Shujah; Hennerici, Michael G.; Ringleb, Peter A.; Veltkamp, Roland (Stroke, 2016)
Background and Purpose: Prospective data on the safety of endovascular thrombectomy in acute stroke patients on non-vitamin K antagonist oral anticoagulants are lacking.Methods: Prospective multicenter observational study. Patients with ischemic stroke undergoing thrombectomy with or without preceding thrombolysis were enrolled into the Registry of Acute Ischemic Stroke Under New Oral Anticoagulants. Baseline characteristics and functional outcome at 3 months were assessed. Hemorrhagic transformation and symptomatic intracranial hemorrhage were analyzed. Reperfusion was graded using the modified Thrombolysis in Cerebral Infarction score.Results: Of 28 patients treated with thrombectomy, 5 had received also systemic thrombolysis (18%). Intracranial hemorrhage was observed in 46%, but symptomatic intracranial hemorrhage occurred only in 1 patient. Successful reperfusion (Thrombolysis in Cerebral Infarction score, 2b-3) was achieved in 59%. At 3 months, 19% had a modified Rankin Scale score of 0 to 2, and mortality was 26%.Conclusions: Thrombectomy in non-vitamin K antagonist oral anticoagulant patients seems safe although a comparatively high rate of asymptomatic hemorrhagic transformation was noted. Confirmation in larger prospective controlled cohorts is necessary.
Gesehen am 18.04.2019